2022
DOI: 10.1021/acsbiomaterials.1c01486
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Cells in a Collagen Matrix Surrounded by an Alginate Hydrogel Shell for 3D Cell Culture

Abstract: Numerous techniques for mammalian cell culture have been developed to mimic the complex in vivo three-dimensional structure of tissues and organs. Among them, the sole use of proteins to create a matrix where cells are embedded already gives rise to self-organized multicellular assemblies. Loading cells in a controlled extracellular matrix along with cell culture and monitoring through a strategy that is compatible with pipetting tools would be beneficial for high throughput screening applications or simply fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In addition to oil and probiotic encapsulation, extrusion has been used for the encapsulation of various other ingredients. For instance, cells encapsulation using the coextrusion technology is one of the most promising methods for three-dimensional cell culture that mimics in vivo the three-dimensional structure of tissues and organs [87].…”
Section: Encapsulation Of Other Ingredientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to oil and probiotic encapsulation, extrusion has been used for the encapsulation of various other ingredients. For instance, cells encapsulation using the coextrusion technology is one of the most promising methods for three-dimensional cell culture that mimics in vivo the three-dimensional structure of tissues and organs [87].…”
Section: Encapsulation Of Other Ingredientsmentioning
confidence: 99%
“…The core-shell structure appears to be superior to other bead structures for long-term cell culture and for three-dimensional self-assembled cellular structures formation [88]. A semipermeable shell is necessary to provide a favorable microenvironment for the cells, with excellent permeability for mass transfer [87][88][89]. It ensures minimal solute diffusion and peripheral cells' escape through the shell.…”
Section: Encapsulation Of Other Ingredientsmentioning
confidence: 99%
“…These benecial features for cell growth has long rendered elastic capsules valuable for applications in human cell culture. [25][26][27] For instance, Nebel et al managed to encapsulate and grow mesenchymal stem cells (MSCs) inside alginate-based elastic capsules using simple inverse gelation for capsule formation. Proliferation measurement showed that the cell number increased 2.5 times aer four days.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Such models include cancer cell culture within porous scaffolds, hydrogels, and organ-in-a-chip devices among others. [7][8][9][10] These models, in particular many 3D models, enable the exploration of a broad range of biophysical or biochemical variables that affect tumor behaviors and TME. [11] Notably, the results obtained for in vitro models require validation for their biological relevance.…”
Section: Introductionmentioning
confidence: 99%
“…In many respects, embedding MCSs in hydrogels can be used to mimic many biophysical features of cancer niches in vivo, including certain mechanical support, strong cell-cell junctions, and gradients in nutrient concentration. [8,[12][13][14][15] Hydrogel-based artificial ECMs offer a spectrum of biophysical properties, such as chemical modifications, control over hydrogel mechanical properties, and the ability to design hydrogel shape and topography, whereby artificial cancer niches could be generated and easily modulated for cancer research and TME studies. [16] Nonadhesive surfaces, spin flasks, or rotational bioreactors are used for MCS culture.…”
Section: Introductionmentioning
confidence: 99%